EMPIRICAL STUDY OF IMPOSTOR SYNDROME ACROSS DIFFERENT AGE PERIODS (Web of Teachers: Inderscience Research, 2026)
The study investigated the manifestation of impostor syndrome across different developmental stages. A total of 1,430 respondents participated, of whom 76.7% were female and 23.3% were male. The results revealed statistically significant differences between age groups (H = 16.56; p = 0.002). The highest levels of impostor syndrome were observed in adulthood and late adulthood, while the lowest levels were found in early adolescence and youth. The findings suggest that impostor syndrome tends to intensify with age and highlight its significance for developing effective psychological support and intervention strategies.